Region - Culture - Innovation. Ways into the Knowledge Society. - Loudín, Jiří (Teorie vědy / Theory of Science, 2010)
Review: Gertraud Koch, Bernd Jürgen Warneken: Region – Kultur – Innovation. Wege in die Wissensgesellschaft. Wiesbaden: VS Verlag für Sozialwissenschaft en 2007.